The reception of the Tübingen-Milan School in Brazil - Marcelo, Perine (Revista Archai, 2011)
The communication starts from a reflection on a formula of the Republic (428 E), which speaks of a “city set up according to nature”. The understanding of this formula in its context, in light of the theory of Principles and the homology which this theory states in the work of Plato between the cosmos, the polis and the soul, allows us to understand why the historical existence of the philosopher is a concrete evidence of the reality of the kallipolis built in the logos.